1994
DOI: 10.1089/cbr.1994.9.307
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Time and Dose Dependency of Interleukin-6 Secretion in Response to Low-Dose Subcutaneous Recombinant Interleukin-2

Abstract: Serum concentrations of Interleukin-6 (IL-6) were determined in renal cell carcinoma patients treated with low-dose subcutaneous human recombinant interleukin-2 (rIL-2). In all patients, administration of rIL-2 resulted in a significant increase in IL-6 serum levels to peak values within 4 to 6 hours as measured by enzyme-linked immunosorbent assays (ELISA). Repetitive administration of rIL-2 induced significantly lower IL-6 serum peaks when compared to the initial administration of rIL-2. Cumulative IL-6 rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…However, after 6 h the IL-6 was decreased as compared with the value 1 h earlier. This is in accordance with the results of earlier studies, which indicate that IL-6 level begins to decline somewhere between 4 and 8 h after the onset of infection/inflammation (Meffert et al, 1994;Berger et al, 1997;Feelders et al, 1998).…”
Section: Resultssupporting
confidence: 93%
“…However, after 6 h the IL-6 was decreased as compared with the value 1 h earlier. This is in accordance with the results of earlier studies, which indicate that IL-6 level begins to decline somewhere between 4 and 8 h after the onset of infection/inflammation (Meffert et al, 1994;Berger et al, 1997;Feelders et al, 1998).…”
Section: Resultssupporting
confidence: 93%
“…Moreover, major depression is reported in high frequency as a reason for dose reduction or for stopping immunochemotherapy (Gutterman et al 1982;Janssen et al 1994a;Kirkwood et al 1996;Guilhot et al 1997;Grob et al, 1998;McHutchison et al 1998;Davis et al 1998;Valentine et al 1998;Van Gool et al 1999). Treatment of cancer patients with IL-2 increases the plasma concentrations of IL-6 and the soluble IL-2 receptor (IL-2R), a T cell activation marker, whereas IFN ␣ increases plasma IL-2 (Janssen et al 1994b;Meffert et al 1994;Taylor and Grossberg 1998).…”
Section: Treatment With Il-2 With or Without Ifn ␣ Significantly Suppmentioning
confidence: 99%
“…25 Meffert et al found repetitive administration of recombinant IL-2 induced significantly lower IL-6 serum peaks, when compared with the initial administration. 26 Adaptive responses to stimuli have also been shown in TNF-α, where additional lipopolysaccharide injections administered within 3 days gave peak measures of 15% of the concentration detected after the first injection. 27 The refractory nature of IL-6 may also be attributed to its short half-life.…”
Section: Discussionmentioning
confidence: 93%